Fixed Points Approximation and Solutions of Some Equilibrium and Variational Inequalities Problems - Bashir Ali (International Journal of Mathematics and Mathematical Sciences)
We prove a new strong convergence theorem for an element in the intersection of the set of common fixed points of a countable family of nonexpansive mappings, the set of solutions of some variational inequality problems, and the set of solutions of some equilibrium problems using a new iterative scheme. Our theorem generalizes and improves some recent results.